A Study on Elusive Enactment of BigData Analytics at University Level - Kumbhar Gajanan Shankar,; Prof (Dr) Virendra Kumar Sharma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In previous years big data applications are increasing everywhere which also forces education sector especially at university level to use big data for prediction of student performance and retention rate among college students at university. As technology changes at very fast speed big data analytics implementation in education will provide new ways of thinking. In this research paper tries to evaluate how big data analytics can be used for student’s performance evaluation and retention at university level. At university level students enrolling for various advanced studies are day by day increasing. Big data refers to large volume of data with technology and tools which are used to process and evaluate this large volume data which may be structured or unstructured format into insightful information for university. This paper tries to address the retention rate issue, history of big data, analytics methodologies for success at any university level students.
Keywords: Big data; University; student performance; Analytics